UJI DAYA HAMBAT EKSTRAK KAYU MANIS (Cinnamomum burmannii) TERHADAP PERTUMBUHAN Candida albicans PADA GIGI TIRUAN AKRILIK - Khatima, Rezky Khusnul; Chotimah, Chusnul; Eva, Andy Fairuz Z. (Jurnal Ilmiah As-Syifaa, 2017)
Background: Denture stomatitis is one of the manifestation of oral candidiasis caused by the use of denture at night, broken dentures, or denture is not kept clean. If the number of Candida albicans increase beyond the normal limit, then within a certain time Candida albicans will be attached to the denture base and will cause infections of the denture wearer in the form of denture stomatitis that could interfere with the comfort and health of the denture wearer. Cinnamomum burmannii as a natural ingredient has an effect as an anti-fungal, anti-viral, anti-bacterial, and larvasidal. Objective: To investigate the inhibition test of extracts of (Cinnamomum burmanii) on the growth of Candida albicans contained in the acrylic denture as one alternative to denture cleaning agents. Materials and Methods: This study was conducted using laboratory experimental method and using design Post test only control group design. Samples were Candida albicans taken from the denture acrylic, then test the inhibition in the Laboratory of Microbiology, Faculty of Pharmacy UMI. Results: Based on the statistical test showed that the zone of inhibition of cinnamon extract on all the different concentrations and had no significant difference in any concentration. Conclusion: Average inhibition cinnamon extract on different concentrations (20%, 30%, 40% and 50%) had noÂ  significant difference to the growth of the Candida albicans in acrylic denture, but have similar effectiveness to the inhibition of the Candida albicans. Extract of cinnamon (Cinnamomum burmannii) at concentration of 20%, 30%, 40%, and 50% showed differences in inhibition is more effective than standard drugs commonly used are (Chlorhexidine 0.2%). Inhibition of Candida albicans will increase along with the increase in the levels of concentration of extract of (Cinnamomum burmannii).